The Effect of Virtual Reality on Pain and Anxiety During Colonoscopy: A Randomized Controlled Trial - Karaveli Çakır, Selda; Evirgen, Sami (Turkish Journal of Gastroenterology, 2021)
Background: The aim of the study is to evaluate the effect of virtual reality application during a colonoscopy on the pain and anxietyexperienced by patients.Methods: The study was conducted as experimental, randomized, controlled research. The study was carried out between October 15,2017 and May 20, 2018 in the Endoscopy Unit of a Public Hospital in northern Turkey. The study sample consisted of 60 patients whounderwent colonoscopy. The patients were divided into 2 groups by using simple randomization. The patients in the experimental groupwatched virtual reality applications during colonoscopy, whereas the patients in the control group underwent standard colonoscopy protocol.Colonoscopy was performed on patients in both groups by the same gastroenterologist without the use of anesthesia. The demographicdata of both groups, pain levels during and after the procedure, before and after the procedure anxiety levels were evaluated.Results: The mean age of the patients in the experimental group was 56.33 ± 11.81, the mean age of the patients in the control groupwas 56.20 ± 15.62. There was no statistically significant difference between the pre- and post-operative state anxiety score averagesof the patients in the experimental and control groups. There was a statistically significant difference between the trait anxiety scores(P < .000) and pain scores (P < .03) during the procedure between both groups.Conclusion: The virtual reality application was found to reduce patients’ pain during the colonoscopy procedure. The virtual realityapplication, an easily available, inexpensive, and non-invasive method, can be used by nurses in pain management during colonoscopy.